If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2b + -1) = 4(3b + -2) Reorder the terms: 5(-1 + 2b) = 4(3b + -2) (-1 * 5 + 2b * 5) = 4(3b + -2) (-5 + 10b) = 4(3b + -2) Reorder the terms: -5 + 10b = 4(-2 + 3b) -5 + 10b = (-2 * 4 + 3b * 4) -5 + 10b = (-8 + 12b) Solving -5 + 10b = -8 + 12b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-12b' to each side of the equation. -5 + 10b + -12b = -8 + 12b + -12b Combine like terms: 10b + -12b = -2b -5 + -2b = -8 + 12b + -12b Combine like terms: 12b + -12b = 0 -5 + -2b = -8 + 0 -5 + -2b = -8 Add '5' to each side of the equation. -5 + 5 + -2b = -8 + 5 Combine like terms: -5 + 5 = 0 0 + -2b = -8 + 5 -2b = -8 + 5 Combine like terms: -8 + 5 = -3 -2b = -3 Divide each side by '-2'. b = 1.5 Simplifying b = 1.5
| 3x-5=-2x+6 | | 169x^2=81 | | 162x^2=80 | | -24-2x+x^2=0 | | 12x-2=5x-8 | | y=6-(x+9)+2x | | 20x+2=48 | | 3x-6(x-17)=66 | | 10t-4=2-8t | | 5x-8x=4x+10 | | 3(b-4)=b-8 | | (5x+2)(5x+2)=48 | | 6x+6(x+5)=90 | | 11x+15=3x+32 | | 6w^2=600 | | -3(2x+5)=-X+5 | | (5v^2)= | | 2(2x+2)=6x+10-12 | | 5k-(3+k)=-(5k+3) | | 159=-6x-5(3x+6) | | x^2-4ix-2=0 | | x^2+x^2+2x=364 | | x^2+x+.25=15.93945+.25 | | x^2-x+.25=15.93945+.25 | | 3x+2(3)=60 | | 4x^2-43x+88=0 | | 3x-5y=-46 | | 4x-14=-34 | | w+-7=3 | | 5833x+x=210355 | | pi=2.14 | | 3x^2+6x-4= |